2015
DOI: 10.1152/jn.00458.2015
|View full text |Cite
|
Sign up to set email alerts
|

Augmented supraorbital skin sympathetic nerve activity responses to symptom trigger events in rosacea patients

Abstract: Facial flushing in rosacea is often induced by trigger events. However, trigger causation mechanisms are currently unclear. This study tested the central hypothesis that rosacea causes sympathetic and axon reflex-mediated alterations resulting in trigger-induced symptomatology. Twenty rosacea patients and age/sex-matched controls participated in one or a combination of symptom triggering stressors. In protocol 1, forehead skin sympathetic nerve activity (SSNA; supraorbital microneurography) was measured during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 44 publications
(25 reference statements)
0
32
0
2
Order By: Relevance
“…In general, a wide range of TEWL values was reported (11·5–35·8 g m ‐2 h −1 ). Patients showed higher TEWL values compared with controls . However, some studies showed no differences at the nasolabial fold, lateral chin, forehead and nose .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In general, a wide range of TEWL values was reported (11·5–35·8 g m ‐2 h −1 ). Patients showed higher TEWL values compared with controls . However, some studies showed no differences at the nasolabial fold, lateral chin, forehead and nose .…”
Section: Resultsmentioning
confidence: 89%
“…Transepidermal water loss (TEWL) was assessed in 16 studies . TEWL is widely accepted as a reference parameter to investigate epidermal permeability barrier function .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not always made at high temperatures. 36 Clinically, a-adrenergic or b-adrenergic receptors blockers contribute to telangiectasia by modulating neuronal dysregulation in rosacea. 31 Therefore, we thought the risks of tea may be because of its own properties.…”
Section: Discussionmentioning
confidence: 99%
“…Vermutlich reagieren betroffene Patienten stärker und länger auf physiologische oder pathophysiologische Stimuli, was zu einer Aktivierung des autonomen und/oder sensorischen Nervensystems der Haut führt . Ionenkanälen vom Typ TRP ( transient receptor potential ) auf Nerven und/oder Endothelzellen , Stickstoffmonoxid (NO) und Neuropeptiden wie Substanz P oder PACAP ( pituitary adenylate cyclase‐activating polypeptides ) kommen hierbei wahrscheinlich eine kritische Bedeutung zu.…”
Section: Pathogeneseunclassified